Kajian Yuridis Terhadap Transaksi Jual Beli Online Dengan Menggunakan Fitur Paylater - Hijriyanti Hijriyanti; Teng Berlianty; Sarah Selfina Kuahaty (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Shopee Paylater is a payment method which means users or consumers will get loans instantly. Each agreement of the parties has an obligation to fulfill achievements to other parties, in practice some of the Consumers do not carry out their obligations properly and correctly, some of the Consumers are not in good faith when carrying out product or service transactions, there are also buyers who do not pay in accordance with the agreed maturity date, therefore the Consumer is deemed to have defaulted.Purposes of the Research: Analyze and review the dispute resolution process if the consumer defaults on the Shopee Paylate payment method. Methods of the Research: : This research is included in normative legal research, namely research examining various positive legal provisions, various legal principles, legal principles and doctrines to answer legal issues faced by.Results of the Research: The results of the study show that the The procedure for carrying out online buying and selling transactions through Shopee using the Paylater feature can be done with the payment method in cash or installments. Furthermore, the process of resolving consumer disputes who default on paylater on the shopee marketplace is by paying a fine of 5% of the total bill and will continue to increase if it is not paid, consumers cannot checkout through shopee and the existing shopee paylater limit will be reduced because of this. the. does not carry out dispute resolution methods through litigation or non-litigation, the Shopee Paylater organizer only takes steps to resolve the dispute internally and provides administrative sanctions for defaulters on the Shopee Paylater usage agreement.